1999
DOI: 10.2139/ssrn.190791
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy, Parameter Uncertainty and Optimal Learning

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…This result is a consequence of the speci…c approach used in this paper to account for model uncertainty, in which the policy instrument can generate interactions between the variables of interest in directions that are precluded in the individual models. This …nding is consistent with a number of previous works studying monetary policy in contexts characterized by imperfect knowledge of the true data generating process, which also concluded that uncertainty might induce an attenuated policy response to economic variables (see, for instance, Brainard, 1967;Wieland, 2000a;Svensson, 1999;Rudebusch, 2001; Söderström, 2000, Tetlow andvon zur Muehlen, 2001 for the case of structured model uncertainty). 2 This paper contributes to the existing literature in economics in several aspects.…”
Section: Introductionsupporting
confidence: 91%
“…This result is a consequence of the speci…c approach used in this paper to account for model uncertainty, in which the policy instrument can generate interactions between the variables of interest in directions that are precluded in the individual models. This …nding is consistent with a number of previous works studying monetary policy in contexts characterized by imperfect knowledge of the true data generating process, which also concluded that uncertainty might induce an attenuated policy response to economic variables (see, for instance, Brainard, 1967;Wieland, 2000a;Svensson, 1999;Rudebusch, 2001; Söderström, 2000, Tetlow andvon zur Muehlen, 2001 for the case of structured model uncertainty). 2 This paper contributes to the existing literature in economics in several aspects.…”
Section: Introductionsupporting
confidence: 91%
“…For instance, Sargent and Williams (2005) study the e¤ect of priors on escape dynamics in a model where the government is learning. Wieland (2000) adapts the framework of Nyarko and Kiefer (1989) to study optimal control by a monetary authority when the authority is a Bayesian learner. We do not have any policy in this paper and so we cannot address these topics.…”
Section: Recent Related Literaturementioning
confidence: 99%
“…Research on passive and active learning stochastic control of economic models has been underway for more than thirty years dating back to the early work of Prescott (1972), MacRae (1972) and Taylor (1974) and including work by Norman (1976), Kendrick (1976Kendrick ( , 1980Kendrick ( , 1981, Easley and Kiefer (1988), Kiefer (1989), Kiefer and Nyarko (1989), Tucci (1989), Mizrach (1991), Aghion et al (1991), Amman (1996), Amman andKendrick (1995, 1997), Wieland (2000aWieland ( , 2000b, Beck and Wieland (2002), Tucci (2004), Cosimano andGapen (2005b, 2005a), Cosimano (2008), Tesfaselassie, Schaling and Eijffinger (2007) and others. What have we learned about learning from this research?…”
Section: What We Have Learnedmentioning
confidence: 99%
“…Wieland presented a dynamic programming method with numerical approximation of optimal decision rules, Wieland (2000aWieland ( , 2000b, that is based on previous work on authors such as Prescott (1972), Taylor (1974) and Kiefer (1989). Cosimano discussed his perturbation method applied in the neighborhood of the augmented linear regulator problem (see Cosimano (2008) and Cosimano andGapen (2005b, 2005a) which draws on work by Hansen and Sargent (2001, 2008.…”
Section: What We Hope To Learnmentioning
confidence: 99%